2019
DOI: 10.1111/obr.12916
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive training on eating behaviour and weight loss: A meta‐analysis and systematic review

Abstract: Cognitive deficits play a role in the development and maintenance of overeating and obesity, and cognitive training in obesity refers to a family of interventions aimed at reducing overeating and obesity by improving these cognitive deficits. In this review, we synthesize the current literature on these issues by conducting a meta-analysis of studies investigating the effects of cognitive trainings on eating behaviour and presenting a systematic review of studies investigating the effects of cognitive training… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
55
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(62 citation statements)
references
References 61 publications
5
55
1
1
Order By: Relevance
“…62 Another meta-analysis investigating 13 AAT interventions found no significant effects of the AAT on eating behaviour, suggesting varying AAT methodology and thus decreased reliability. 63 Second, the present study lacked a non-food control condition with the AAT, making it difficult to determine whether the effects that we saw were specific to food rewards. There was also no clear-cut separation in terms of calories or processed foods or snacks vs main meals, and this should be consider in future studies with respect to stimulus development.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…62 Another meta-analysis investigating 13 AAT interventions found no significant effects of the AAT on eating behaviour, suggesting varying AAT methodology and thus decreased reliability. 63 Second, the present study lacked a non-food control condition with the AAT, making it difficult to determine whether the effects that we saw were specific to food rewards. There was also no clear-cut separation in terms of calories or processed foods or snacks vs main meals, and this should be consider in future studies with respect to stimulus development.…”
Section: Discussionmentioning
confidence: 94%
“…A meta‐analysis of 29 AAT studies suggested that the instructions given to participants (eg, instructed to focus on task‐relevant content vs to attend to an irrelevant feature) played an important role in the non‐significant overall effects 62 . Another meta‐analysis investigating 13 AAT interventions found no significant effects of the AAT on eating behaviour, suggesting varying AAT methodology and thus decreased reliability 63 . Second, the present study lacked a non‐food control condition with the AAT, making it difficult to determine whether the effects that we saw were specific to food rewards.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, training effects cannot be accounted for by Pavlovian, evaluative, or operant conditioning alone, where objects or behaviors are paired with events with clear evaluative connotations (De Houwer, 2007). Instead, GNG was first introduced as a training of inhibitory control (Houben & Jansen, 2011) and is still presented as such (e.g., Allom et al, 2016;Carbine & Larson, 2019;Forman et al, 2019;Jones et al, 2016;Yang et al, 2019). BEYOND INHIBITORY CONTROL TRAINING 4 According to this account, repeatedly not responding to attractive objects serves as an exercise to train the brain to become better at executing control in order to resist temptations.…”
Section: Beyond Inhibitory Control Trainingmentioning
confidence: 99%
“…Finally, it is doubtful whether executive control can be trained with such a simple training procedure (Veling et al, 2017). In light of these findings and arguments, the current and consistent portrayal of GNG as an inhibitory control training (e.g., Carbine & Larson, 2019;Forman et al, 2019;Yang et al, 2019) is remarkably tenacious. A lack of convincing evidence for alternative explanations may contribute to this status quo.…”
Section: Beyond Inhibitory Control Trainingmentioning
confidence: 99%
“…CBM paradigms targeting interpretation bias (CBM-I) foster positive (i.e., unbiased, balanced, or self-serving) interpretations of ambiguous information [18,19]. Despite mixed results in meta-analyses [20,21], CBM-I has shown potential to reduce psychopathology [22]. So far, seven studies have examined CBM-I in the domain of body image/ eating disorders (for review see [19]), of which four studies investigated appearance-based CBM-I approaches [23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%